2022
DOI: 10.3389/fonc.2022.939965
|View full text |Cite
|
Sign up to set email alerts
|

Metastases to the thyroid gland: ultrasonographic findings and diagnostic value of fine-needle aspiration cytology

Abstract: IntroductionIn the present study, we aimed to analyze ultrasonographic findings of metastases to the thyroid and explore the role of fine-needle aspiration cytology (FNAC) in the diagnosis of metastases to the thyroid.MethodsTwelve cases of cytologically or/and pathologically confirmed metastatic tumors of the thyroid gland were reviewed. All the primary thyroid lesions and lymphomas were excluded. The location, maximum size, echogenicity, shape, margin, presence of calcifications, vascularity, and cervical ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 35 publications
1
7
1
Order By: Relevance
“…A search in Pubmed found only 9 studies on SMTG containing at least 8 cases with the following keywords (FNA biopsy, metastatic, thyroid, and secondary). [17][18][19][20][21][22][23][24][25] In contrast, the number of cases included in our study was higher and the clinical information and IHC-related data were more comprehensive.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A search in Pubmed found only 9 studies on SMTG containing at least 8 cases with the following keywords (FNA biopsy, metastatic, thyroid, and secondary). [17][18][19][20][21][22][23][24][25] In contrast, the number of cases included in our study was higher and the clinical information and IHC-related data were more comprehensive.…”
Section: Discussionmentioning
confidence: 99%
“…These adenocarcinoma cell clusters had more pronounced nuclear heterogeneity when compared with PTC. 20,29 Metastatic renal carcinomas were the most common pitfall in previous series. 18,22 Smears of metastatic breast and renal carcinomas usually show mild and moderate cellular atypia; therefore, previous studies have suggested that metastases of renal and breast adenocarcinomas were almost indistinguishable from follicular tumor and PTC on cytologic grounds.…”
Section: Cytologic Features Of Smtgmentioning
confidence: 94%
See 3 more Smart Citations